2010
DOI: 10.1177/1759720x10374437
|View full text |Cite
|
Sign up to set email alerts
|

The FIBRO System: a rapid strategy for assessment and management of fibromyalgia syndrome

Abstract: Fibromyalgia syndrome (FMS) is a complex disorder of widespread pain and tenderness associated with numerous other symptoms including fatigue, cognitive dysfunction, nonrestorative sleep, depression, anxiety, and stiffness. While new diagnostic criteria and previous management guidelines require quantitation of the severity of associated FMS symptoms experienced by individual patients, no system for rapid patient assessment has been made available to provide a basis for diagnosis, treatment selection and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
6
0
1
Order By: Relevance
“…VASFIQ completion requires self-administration of a paper questionnaire and VAS scoring requires distance measurement with a ruler, both of which can be cumbersome to perform in the clinic setting. Oral administration of the VASFIQ using a 010 numeric rating scale has been proposed as a way to circumvent these issues [Boomershine, 2010;Boomershine and Crofford, 2009]. However, since oral administration would require changes to the VASFIQ, including addition of a small introductory explanation and third-person wording of the items, validation of an interviewer-administered version is needed before it can be recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VASFIQ completion requires self-administration of a paper questionnaire and VAS scoring requires distance measurement with a ruler, both of which can be cumbersome to perform in the clinic setting. Oral administration of the VASFIQ using a 010 numeric rating scale has been proposed as a way to circumvent these issues [Boomershine, 2010;Boomershine and Crofford, 2009]. However, since oral administration would require changes to the VASFIQ, including addition of a small introductory explanation and third-person wording of the items, validation of an interviewer-administered version is needed before it can be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important limitation of using VASs in FM management, because medications that improve some FM symptoms often worsen other symptoms and many patients with FM have high baseline VAS scores. A revision of the VASFIQ that utilizes more extreme wording for the upper anchors to decrease ceiling effects and a patient impression of change format at follow up has been proposed to improve assessment of symptom worsening in patients with FM [Boomershine, 2010], but this revision needs to be validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have suggested that for clinical practice (and probably for research), a common set of simple variables that can be used across all rheumatic diseases and pain illness, rather than disease-specific variables, can be an effective way to evaluate patients 31 . Boomershine has reviewed comprehensive assessment tools in FM 32 and proposed a 7-item VAS scale assessment tool based on an older, shortened version of the FIQ 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Mit dieser besonders günstigen Art der Evaluation von Therapieveränderungen kann der sogenannte high ceiling effect umgangen werden, da bei schwerer Symptomatik und entsprechend maximalen Baseline-Werten durch Interventionen bewirkte Verbesserungen oder Verschlechterungen der Beschwerden erneut mit der Angabe maximaler Werte einhergehen und so durch eine Therapie erzielte Veränderungen nicht erfasst werden können. Der FCS enthält 7 numerische Rangskalen (NRS), welche die Kernsymptome Schmerz, Erschöpfung/Müdigkeit, Schlaf, Depression, innere Unruhe/Nervosität, Steifigkeit und kognitive Dysfunktion erfassen [20,23]. Die 7 Elemente des validierten FCS wurden in dieser Studie um ein weiteres ergänzt, das die Veränderungen der lokalen Schmerzintensität im Bereich der Ellenbogen erfasst (FCS lokal).…”
Section: Methodik Und Studiendesignunclassified